The Effectiveness of Lumbung Hidup in Improving Toddler Nutrition Among Economically Disadvantaged Families - Reni Nurhidayah; Dhita Kurnia Sari; Prima Dewi Kusumawati (Journal of Global Research in Public Health, 2024)
Malnutrition and stunting are significant issues among economically disadvantaged families in Kediri District, affecting children's health and development. This study assessed the Lumbung Hidup program, which established kitchen gardens and catfish farming to improve nutrition. Using a pre-experimental one-group pre-test post-test design, 22 toddlers with low body weight and stunting were monitored over three months. Pre-test data were collected before, and post-test data after the intervention. The intervention led to significant improvements in nutritional status. Mean weight increased from 11.25 kg (pre-test) to 14.48 kg (post-test 3), and mean height slightly increased from 89.29 cm to 89.98 cm. Paired sample t-tests showed significant enhancements in Z-scores for weight-for-age, height-for-age, and weight-for-height (p < 0.05). The Lumbung Hidup program effectively improved the nutritional status of toddlers from economically disadvantaged families, demonstrating potential for broader implementation to combat malnutrition and stunting.